Osofisan's thunder-king and the recreation of Ladipo‘s sango (2017)
Adaptation as a literary art in its entirety has been described as a mimetic art. The enterprise of reshaping and recreating a text, context and co-text from its original form to suit a new context, space, time or culture is the other element of adaptation which could take on the inter or intra cultural regalia. Femi Osofisan's folio includes dynamic inter and intra cultural adaptations; most of which have been studied across theatrical and critical contexts. This study examines his re-creative engagement of the Yoruba Thunder God, Sango, a character magically transformed from Yoruba history and legend into the contemporary theatrical life in Duro Ladipo's Oba Ko So. This study examines the demystification of the Thunder God and his queens, who are also prominent deities among the Yoruba pantheon. It comparatively examines the gaps Osofisan's Many Colours Make a Thunder- King fills along the observable and discernable convergence and divergence in the sinews of adaptation evident in the dynamic adaptation of characterology, thematic centring, plot structure and form in both plays. The triggers of Osofisan's exploration and craft are intriguing as he celebrates and interrogates existing texts and philosophies and, in this case, extending the philosophical, historical as well as gender related arguments in his recreation of the Thunder God and his queens.